Renal Allograft Survival in Nonhuman Primates Infused With Donor Antigen‐Pulsed Autologous Regulatory Dendritic Cells. Issue 6 (2nd February 2017) - Ezzelarab, M. B.; Raich‐Regue, D.; Lu, L.; Zahorchak, A. F.; Perez‐Gutierrez, A.; Humar, A.; Wijkstrom, M.; Minervini, M.; Wiseman, R. W.; Cooper, D. K. C.; Morelli, A. E.; Thomson, A. W.
Abstract : Systemic administration of autologous regulatory dendritic cells (DCreg; unpulsed or pulsed with donor antigen [Ag]), prolongs allograft survival and promotes transplant tolerance in rodents. Here, we demonstrate that nonhuman primate (NHP) monocyte‐derived DCreg preloaded with cell membrane vesicles from allogeneic peripheral blood mononuclear cells induce T cell hyporesponsiveness to donor alloantigen (alloAg) in vitro . These donor alloAg‐pulsed autologous DCreg (1.4–3.6 × 10 6 /kg) were administered intravenously, 1 day before MHC‐mismatched renal transplantation to rhesus monkeys treated with costimulation blockade (cytotoxic T lymphocyte Ag 4 immunoglobulin [CTLA4] Ig) and tapered rapamycin. Prolongation of graft median survival time from 39.5 days (no DCreg infusion; n = 6 historical controls) and 29 days with control unpulsed DCreg (n = 2), to 56 days with donor Ag‐pulsed DCreg (n = 5) was associated with evidence of modulated host CD4 + and CD8 + T cell responses to donor Ag and attenuation of systemic IL‐17 production. Circulating anti‐donor antibody (Ab) was not detected until CTLA4 Ig withdrawal. One monkey treated with donor Ag‐pulsed DCreg rejected its graft in association with progressively elevated anti‐donor Ab, 525 days posttransplant (160 days after withdrawal of immunosuppression). These findings indicate a modest but not statistically significant beneficial effect of donor Ag‐pulsed autologous DCreg infusion on NHP graft survival when administered with a minimal immunosuppressive drug regimen. Abstract : This study demonstrates a modest beneficial effect of donor antigen‐pulsed autologous regulatory dendritic cell infusion on nonhuman primate renal allograft survival when administered with a minimal immunosuppressive drug regimen.